Three-Dimensional Architecture and Biogenesis of Membrane Structures Associated with Plant Virus Replication - Jin, Xuejiao; Cao, Xiuling; Wang, Xueting; Jiang, Jun; Wan, Juan; Laliberté, Jean-François; Zhang, Yongliang (Frontiers in Plant Science, 2018)
Positive-sense (+) RNA viruses represent the most abundant group of viruses and are dependent on the host cell machinery to replicate. One remarkable feature that occurs after positive-sense (+) RNA virus entry into cells is the remodeling of host endomembranes, leading to the formation of viral replication factories. Recently, rapid progress in three-dimensional (3D) imaging technologies, such as electron tomography (ET) and focused ion beam-scanning electron microscopy (FIB-SEM), has enabled researchers to visualize the novel membrane structures induced by viruses at high resolution. These 3D imaging technologies provide new mechanistic insights into the viral infection cycle. In this review, we summarize the latest reports on the cellular remodeling that occurs during plant virus infection; in particular, we focus on studies that provide 3D architectural information on viral replication factories. We also outline the mechanisms underlying the formation of these membranous structures and discuss possible future research directions.